Adrenal insufficiency in kidney transplant patients during low-dose prednisolone therapy: a cross-sectional case–control study. Issue 12 (20th September 2019) - Valentin, Amalie; Borresen, Stina Willemoes; Rix, Marianne; Elung-Jensen, Thomas; Sørensen, Søren Schwartz; Feldt-Rasmussen, Ulla
Abstract: Background: Maintenance immunosuppressive regimens after renal transplantation (RTx) most often include prednisolone, which may induce secondary adrenal insufficiency, a potentially life-threatening side effect to glucocorticoid (GC) treatment due to the risk of acute adrenal crisis. We investigated the prevalence of prednisolone-induced adrenal insufficiency in RTx patients receiving long-term low-dose prednisolone treatment. Methods: We performed a case–control study of patients on renal replacement therapy differing in terms of GC exposure. The study included 30 RTx patients transplanted >11 months before enrolment in the study and treated with prednisolone (5 or 7.5 mg prednisolone/day for ≥6 months) and 30 dialysis patients not treated with prednisolone. Patients underwent testing for adrenal insufficiency by a 250-µg Synacthen test performed fasting in the morning after a 48-h prednisolone pause. Normal adrenal function was defined as P-cortisol ≥420 nmol/L 30 min after Synacthen injection. This cut-off is used routinely for the new Roche Elecsys Cortisol II assay and is validated locally based on the Synacthen test responses in 100 healthy individuals. Results: Thirteen RTx patients {43% [95% confidence interval (CI) 27–61]} had an insufficient response to the Synacthen test compared with one patient in the control group [3% (95% CI 0.6–17)] (P = 0.0004). Insufficient responses were seen in 9/25 and 4/5 RTx patients treated with 5 and 7.5 mg prednisolone/day, respectively. Conclusions: We found a high prevalence of adrenal insufficiency among RTx patients receiving low-dose prednisolone treatment. We therefore advocate for increased clinical alertness towards prednisolone-induced adrenal insufficiency in RTx patients and thus their potential need of rescue GC supplementation during stress.